Interface reaction and mechanical properties of Sn58Bi-XCr/Cu30Zn (Cu7Sn) solder joints under isothermal aging conditions. (November 2022) - Song, Qianqian; Li, Anmin; Qi, Da; Qin, Weiou; Li, Yitai; Zhan, Yongzhong
Abstract: The interfacial reaction and mechanical properties of Sn58Bi-XCr/Cu30Zn and Sn58Bi-XCr/Cu7Sn (X = 0, 0.1, 0.2, 0.3 wt%) composite solder joints were investigated under 100 °C isothermal aging. The results show that the growth rate of intermetallic compound layer (IMCs) of Sn58Bi-XCr/Cu30Zn composite solder joint is faster than that of Sn58Bi-XCr/Cu7Sn composite solder joint, and the rapid growth of IMCs decreases the mechanical properties of the solder joint. As the aging time increases, the thickness of IMCs layer becomes thicker and the mechanical properties decrease. The addition of Cr inhibits the interdiffusion of atoms at the interface. The addition of Zn/Sn reduces the consumption of Sn and thus reduces the segregation of Bi phase. The Bi segregation at the interface of Sn58Bi-0.2Cr/Cu30Zn and Sn58Bi-0.2Cr/Cu7Sn composite solder joints is improved obviously. In addition, the comprehensive mechanical properties of Sn58Bi-XCr/Cu30Zn composite solder joint are higher than those of Sn58Bi-XCr/Cu7Sn composite solder joint. With the extension of aging time, mechanical strength increases first and then decreases. Among them, the mechanical strength of Sn58Bi-0.2Cr/Cu30Zn and Sn58Bi-0.2Cr/Cu7Sn composites is superior to other alloys. The fracture morphology of solder joints changes from brittle fracture mechanism to ductile-brittle fracture mechanism. Highlights: The addition of Cr particles hinders the interdiffusion of atoms during the interfacial reaction. Adding a small amount of the second element to the Cu substrate can eliminate the segregation of the brittle Bi-phase at the interface. The growth rate of the IMCs layer of the Sn58Bi-XCr/Cu30Zn composite solder joint is is relatively high. The existence of Cu–Zn intermetallic compounds can improve the mechanical strength of Sn58Bi-XCr solder joints.